(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
The recommendation by the Basic Education Ministerial Task Team to phase in history as a compulsory school subject from Grades 10 to 12 in the Further Education and Training (FET) phase has been one of the most controversial curriculum topics in South Africa in recent years. This uproar can be connected to the fact that the importance of history as a school subject has been topical at local and international levels including certain countries phasing out the subject. This study aimed to establish the views of history teachers from the Frances Baard District on the effectiveness of the call to make history a compulsory subject in South Africa particularly during the FET phase. This study used a qualitative research approach that employed an interpretive paradigm. Semi-structured interviews were employed for data collection and a thematic analysis technique was used to distinguish different themes. Social constructivism was adopted as the theoretical framework to nuance the findings and determine what influenced the teachers’ perspectives. The findings indicated that history is still full of great worth in the social and academic fabric of South Africa and for this reason it should be made a compulsory subject in school. The study also assumes that implementing history in the FET band will give more dignity to the discipline leading to improved teaching slots and times.